The Role of SME Promotion Agencies in Entrepreneurial Development: An Assessment - Pineda, Ernesto P. (Philippine Management Review, 2016)
This paper assesses the overall effort associated with entrepreneurship development in the Philippines.  The assessment focuses on the Small and Medium Enterprises (SME) sector and the agencies and other entities involved in assisting SMEs.  The University of the Philippines Institute for Small Scale Industries (UP ISSI) model of entrepreneurship development was used to highlight significant activities of the effort.  The assessment showed that the service intensity of some government agencies charged with SME promotion appears to be low because several of them are tasked to do similar functions.  It also identified and discussed areas and issues crucial to entrepreneurship development.